A Study on Demonstrating the Consistency of the Formulation of the Parameters of 5 or Less Independent Variables of Multiple Linear Regression with Data Examples (Journal of Nonlinear Modeling and Analysis, 2025)
In this study, it is aimed to demonstrate the consistency of the previously given formulations of the parameters of 5 or less independent variablesof multiple linear regression with data examples. All the values in the parameter formulas of 5 or less independent variables with respect to one dependentvariable were found to be the same as all the parameter values obtained fromthe related equation system. In other words, the values found with the parameter formulas and the parameter values found with the computer programwere found to be the same.